2001
DOI: 10.1063/1.1347402
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of RuO2 electrodes on Zr silicate and ZrO2 dielectrics

Abstract: Physical and electrical properties of metal gate electrodes on HfO 2 gate dielectrics

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 17 publications
1
28
0
Order By: Relevance
“…On the other hand, we consistently obtain good Ohmic contacts with pulsed laser deposition of RuO 2 (w200 nm) at room temperature [37,38], followed by a layer of Au (w100 nm) via thermal evaporation, which was used to facilitate wire bonding. Consistent formation of Ohmic contacts here is likely due to the metallic behavior of RuO 2 (work function of 5.1 eV [39,40]) and the limitations of interfacial diffusion and reaction at the SnO 2 /RuO 2 interface.…”
Section: Making Ohmic Contacts To Single Sno 2 Nanobeltmentioning
confidence: 88%
“…On the other hand, we consistently obtain good Ohmic contacts with pulsed laser deposition of RuO 2 (w200 nm) at room temperature [37,38], followed by a layer of Au (w100 nm) via thermal evaporation, which was used to facilitate wire bonding. Consistent formation of Ohmic contacts here is likely due to the metallic behavior of RuO 2 (work function of 5.1 eV [39,40]) and the limitations of interfacial diffusion and reaction at the SnO 2 /RuO 2 interface.…”
Section: Making Ohmic Contacts To Single Sno 2 Nanobeltmentioning
confidence: 88%
“…9,10 As an alternative gate electrode for integration with high-ZrO 2 and Zr silicate dielectrics in PMOS devices, excellent stability and electric properties indicated that RuO 2 is a promising candidate for implementation in PMOS devices. 11,12 However, detailed information on the work function of conductive oxides relating to the oxidation state is very limited. 13 When integrating them with alternative high-dielectrics, the unknown band alignment may result in unpredictable electrical properties.…”
mentioning
confidence: 99%
“…[3] Ruthenium-based electrode materials have demonstrated excellent thermal stability not only on silicon dioxide (SiO 2 ), but also on high-dielectric constant (k) materials, such as zirconium oxide (ZrO 2 ), Zr silicates, and yttrium silicates. [4][5][6] Additionally, Ru electrodes for perovskite-based (e.g., Ba x Sr 1-x TiO 3 , PbZr x Ti 1-x O 3 , and SrBi 2 Ta 2 O 9 ) capacitors in random access memories have been the subject of great attention worldwide. Among the various thin-film-deposition techniques in the microelectronics industry, the potential advantages of MOCVD include thickness uniformity over large substrate areas, good conformity or step coverage in complex features, and a high throughput for commercial-scale production.…”
Section: Introductionmentioning
confidence: 99%